Long-term dynamics of placozoan culture: emerging models for population and space biology - Daria Y. Romanova; Alexander A. Povernov; Mikhail A. Nikitin; Simkha I. Borman; Yana A. Frank; Leonid L. Moroz; Leonid L. Moroz (Frontiers in Cell and Developmental Biology)
As the simplest free-living animal, Trichoplax adhaerens (Placozoa) is emerging as a powerful paradigm to decipher molecular and cellular bases of behavior, enabling integrative studies at all levels of biological organization in the context of metazoan evolution and parallel origins of neural organization. However, the progress in this direction also depends on the ability to maintain a long-term culture of placozoans. Here, we report the dynamic of Trichoplax cultures over 11 years of observations from a starting clonal line, including 7 years of culturing under antibiotic (ampicillin) treatment. This study revealed very complex population dynamics, with seasonal oscillation and at least partial correlations with the solar radio emission flux and the magnetic field disturbance parameters. Notable, the analysis of the distribution of Fe2+ in living animals revealed not only its high abundance across most cells but also asymmetric localizations of Fe2+ in unidentified cells, suggesting that these Fe2+ intracellular patterns might be coupled with the animal’s bioenergetics. We hypothesize that placozoans might have magnetoreception, which can be experimentally tested in future studies. In sum, Trichoplax, in particular, and Placozoa, in general, can be viewed as prospective reference species in traditional evolutionary and system biology but have the yet unexplored potential for planetary ecology and space biomedicine.